The Perceived of The Grade 3 Students of Secondary School in Bangkok on Premarital Sex Behavior and Adolescent Pregnancy - Sunanta, Sangjan; Proyngern, Chantana (Journal of The Royal Thai Army Nurses, 2021)
This survey research aimed to determine the perception of the grade 3 students of secondary school in Bangkok on premarital sexual behaviors and adolescent pregnancy. The participants were 180 grade 3 students of secondary school in Bangkok, 90 were male and 90 were female. Data were collected using closed-ended question with 10 items and analysed using content analysis. Mostly participants’ perceived value and attitude on premarital sexual behavior and adolescent pregnancy, the results shown that they should not have sex during school age because of sexual transmitted diseases, unwanted pregnancy, and adverse effects on their studies and families. Male participants perceived that the cultivated values is honor, patience and suppression on their sexual emotions. Female participants perceived that learning to refuse, avoiding dating in private and sexual arousing such as touching, kissing and sexual media can prevent sexual intercourse. The most important of prevention teenage pregnancy that perceived by male and female participants is A B C concept (A: Abstinence means not having sex; B: Be appropriate behaviors; C : Condom using). Moreover, unwanted pregnancy should be informed to their parents, teachers with visiting healthcare center or calling 1663, hotline number for consultation. The study results suggest an application on development of teenage life skills to cope with sexual situations. The cultivated proper sexual value and attitudes should be introduced in the school age by their families, schools, healthcare providers, and policy makers.